Em busca de um modelo de leitura (Revista de Estudos da Linguagem, 2003)
In this paper we discuss some of the cognitive processes involvedin reading, and the relationship among them. We also present areading model, that may be called linear or serial, which is basedon the theory of the modularity of the mind defended by Fodor(1983). Based on criticisms of this model, another is proposed,which, however, supports the parallel processing of the information.We propose as well a review of some concepts involved in thereading process, taking the relevance theory, proposed by Sperberand Wilson (1986/95), as a starting point.